Parent Perception: A Study on Child Viewership of Cartoon Channels - Dubey, Prince; Kumar, Sunil; Siddiquei, Mohd Imran; Muneeb, Syed Mohd; Pushpa, B (International Journal of Psychosocial Rehabilitation, 2020)
Cartoon television programs plays a wide role among children viewership. Children were crazy towards cartoon. They opt the same as cartoon character play in role. Cartoon programmes deals both positive as well as negative. To check what type of impact normally influences cartoon among children. We collect the responses of parents whose children view cartoon programs. It is secondary base data means our study is descriptive research. This research is an attempt to measure the attitudes and behaviours of children. The data analysis is done by using exploratory factor analysis. However, the ultimate goal of this study is to bring awareness among parents towards children viewership that how negatively it shifts children's future towards dark. This study also introduces a parental meditation and its importance now a day. The participants of this study are the parents.The present research shows that the cartoon programmes presenting very impractical ways which distract children's mind. These unrealistic programmes sometimes lead children to make unhealthy decisions and cause confusion to take corrective action. The result shown negative aspects but also somehow positive attitude towards cartoon viewership.